Polyurethane composites with different matrices filled with glass microspheres - Ryszkowska, J.; Zieleniewska, M.; Bryśkiewicz, A; Mizera, K.; Chrząszcz, M.; Kozon, D.; Lipert, K. (Polimery, 2021)
The paper concerns composites made of polyurethane materials intended for the production of molds used in the vacuum casting process (VC). Two types of polyurethanes were applied to prepare the composites filled with glass microspheres. The influence of the filler on the properties of the resulting polyurethane composites was investigated. The viscosity of the premixes for the preparation of these composites was determined. The crosslinked composites were characterized using thermomechanical analysis (DMA), while their structure was investigated by infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). The results of strength tests are also presented.